Association of metformin use with fracture risk in type 2 diabetes: A systematic review and meta-analysis of observational studies - Wang, Yining; Yu, Liming; Ye, Zhiqiang; Lin, Rui; Sun, Antonia RuJia; Liu, Lingna; Wei, Jinsong; Deng, Feifu; Zhong, Xiangxin; Cui, Liao; Li, Li; Liu, Yanzhi (Frontiers in Endocrinology, 2023)
Aims: Increasing evidence suggests that metformin can affect bone metabolism beyond its hypoglycemic effects in diabetic patients. However, the effects of metformin on fracture risk in type 2 diabetes mellitus (T2DM) patients remain unclear. A systematic review and meta-analysis were performed in this study to evaluate the association between metformin application and fracture risk in T2DM patients based on previous studies published until June 2021. Methods: A systematic search was performed to collect publications on metformin application in T2DM patients based on PubMed, Embase, Cochran, and Web of Science databases. Meta-analysis was performed by using a random-effects model to estimate the summary relative risks (RRs) with 95% confidence intervals (CIs). Subgroup analyses based on cohort/case-control and ethnicity and sensitivity analyses were also performed. Results: Eleven studies were included in the meta-analysis. Results demonstrated metformin use was not significantly associated with a decreased risk of fracture (RR, 0.91; 95% CI, 0.81–1.02; I2=96.8%). Moreover, metformin use also demonstrated similar results in subgroup analyses of seven cohort studies and four case-control studies, respectively (RR, 0.90; 95% CI, 0.76–1.07; I2=98.0%; RR, 0.96; 96% CI, 0.89–1.03; I2=53.7%). Sensitivity analysis revealed that there was no publication bias. Conclusion: There was no significant correlation between fracture risk and metformin application in T2DM patients. Due to a limited number of existing studies, further research is needed to make a definite conclusion for clinical consensus.